The Perspectives of Infectious Diseases and Clinical Microbiology Specialists on Online Education Applications and Web-based Seminars - Ozturk Kaygusuz, Turkkan; Agalar, Canan; Kurtaran, Behice; Cag, Yasemin; Tasbakan, Meltem (Galenos Yayincilik, 2021)
Introduction: In this study, it was aimed to obtain information about the perspectives of infectious diseases and clinical microbiology (IDCM) specialists on online education applications and web-based seminars, and their usage and utilization rates. Materials and Methods: In this descriptive, cross-sectional study, online survey responses of the IDCM specialists in who were members of Infectious Diseases Clinical Microbiology Specialty Society of Turkey (EKMUD) were evaluated. Results: A total of 184 IDCM specialists answered the survey questions. Of the participants, 77.2% thought that the pandemic disrupted postgraduate medical education and 84.8% thought that the pandemic disrupted pre-graduate medical education. Medical educators involved in education during the Coronavirus disease-2019 (COVID-19) pandemic reported that they mostly continued online education. Of the participants, 84.9% reported that they were able to use the internet in an effective way to gain access to information during the COVID-19 pandemic. Of the responders, 58.2% reported that they followed online training programs, such as web-based seminars and lectures, and 51.6% reported that these online programs contributed to their learning. Participants found online training programs such as web-based seminars and lectures useful in terms of learning competence, that online training programs provided people with gain in space and time, and that they found them more instructive because they gave them the chance to receive training in subjects of their interest. Participants reported that these programs provided learning competency in that these programs were more beneficial to the participants in view of place, the subject that they need/they are interested in and saving time for the trainer and the participants. Due to the COVID-19 pandemic, the participants mostly wanted the 2020 EKMUD congress to be held online. A total 92.9% of the participants reported that online congresses and seminars would decrease travel, participation and sponsorship costs. Only 24.5% of the participants considered that online congresses and seminars would be more effective in terms of social interaction and gaining information than face-to-face congresses. Conclusion: The IDCM specialists reported that online educational practices such as webinars were benefical. The rate of participation in webinars and online education practices were high during the COVID-19 pandemic.
Enfeksiyon Hastaliklari ve Klinik Mikrobiyoloji Uzmanlarinin Online E?itim Uygulamalarina ve Web Tabanli Seminerlere Bakiş Açilari
Keywords: COVID-19; webinar; web-based conferencing; online medical education; medical education